Anti-Inflammation Effectiveness of Ginger (Kaemferia galanga l.) and Shallots (Allium ascalonicum l.) Extract Combination on Sprague-Dawley Male Rat - Nurmala, Sara; Elfrieda, Nyayu Siti Aminah Lily; Zaddana, Cantika; Ali, Aida Azlina (Universitas Pakuan, 2024)
Inflammation can be caused by various stimuli which include physical injury, infection, heat and antigen antibody interactions. Ginger (Kaempferia galanga L.) and Shallots (Allium ascalonicum L.) are medicinal plants that are often used by Indonesians as an alternative to natural medicine and have been studied to have good anti-inflammatory properties because they contain quercetin. This study aims to determine the effective dose of the combination of Ginger ethanol extract and Shallots as anti-inflammatory with a smaller dose. This study was carried out using male rats in 5 treatment groups, consisting of negative control (CMC-Na 0.5 %), control positive (diclofenac Na tablets 0,1 mg/kg body weight rat), and 3 combination doses of Ginger extract: Shallots extract, dose combination I (3 mg/kg body weight Rat: 2 mg / kg body weight Rat), dose combination II (6 mg / kg body weight Rat : 1 mg/kg body weight Rat), and the dose combination III (6 mg/kg body weight Rat: 2 mg kg body weight Rat) using Carrageenan Method on Rat's Feet. The results of the anti-inflammatory activity test showed that all the dose combination treatment groups had anti-inflammatory. The dose combination III was significantly different from the negative control group and showed the most effective dose of combination. The formulated combination shows a synergistic effect between ginger and shallots as an anti-inflammatory. Average percentage (%) of edema inhibition combination III is 71,08 %.